THE EFFECT OF CLUSTERING TECHNIQUE UPON THE 8TH GRADE STUDENTS' ACHIEVEMENT IN WRITING AT SMP NEGERI 3 KUBUTAMBAHAN IN ACADEMIC YEAR OF 2013/2014 - ., I Dewa Ketut Suputra; ., Ni LP. Eka Sulistia Dewi, S.Pd. M.Pd.; ., Prof. Dr. Anak Agung Istri Ngr. Marha (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini merupakan penelitian eksperimen yang bertujuan untuk menguji pengaruh penggunaan teknik Clustering terhadap prestasi menulis siswa. Teknik sampling yang digunakan adalah teknik sampling acak untuk memilih dua kelas dengan mengacu pada hasil uji normalitas dan hogenitas varian. Model penelitian ini adalah Post Test Only Control Group Design. Instrument yang digunakan untuk memperoleh data dalam penelitian ini adalah tes menulis dan rubrik penilaian. Data kemudian dianalisis dengan menggunakan statistical deskriptif analisis dan statistic inferensial. Nilai rata-rata siswa pada grup belajar dengan teknik Clustering adalah 63.62 yang mana lebih besar dari nilai rata-rata grup convensional (56.50). Berdasarkan hasil dari uji hipotesis, nilai dari to (t observe) adalah 2.468 lebih besar dari nilai tcv (t critical value) yaitu 1.6706 (α = 0.05). Dapat disimpulkan bahwa ada pengaruh yang signifikan dari penggunaan teknik Clustering terhadap prestasi siswa SMP Negeri 3 Kubutambahan dalam menulis.Kata Kunci : Menulis, Prestasi menulis siswa, Teknik Clustering This study was an experimental research which focused on examining whether there is a significant effect of clustering technique upon students’ achievement in writing. In this research, random sampling technique was used to choose the sample from population in which two classes were selected by concerning the normality and homogeneity of variance test. The research design is post test only control group design. The instrument which was used to gain the data in this research is writing achievement test and analytical scoring rubric. The data were analyzed by using descriptive statistical analysis and inferential statistical analysis. The average score of the group learning through clustering technique was 63.62 which is higher than the average score of the conventional group (56.50). Based on the result of hypothesis testing, it was found that the value of t observed (to) was 2.468 in which was higher than t critical value (tcv) was 1.6706 (α = 0.05). It can be concluded that there is significant effect of clustering technique upon the students’ achievement in writing at 8th grade students of SMP Negeri 3 Kubutambahan.keyword : Clustering technique, Writing, Writing Achievement